Mastering Deathlessness: Some Remarks on Kaṟpam Preparations in the Medico-Alchemical Literature of the Tamil Siddhas - Kędzia, Ilona Barbara (History of Science in South Asia, 2017)
The article presents some remarks concerning practices aimed at achieving rejuvenation, longevity and immortality described in the literature of the Tamil Siddhas, with special reference to the medico-alchemical stream of the tradition. The study is based on the philological analysis of selected representative works of Tamil Siddha literature, starting from the Tirumantiram of Tirumūlar (6-12th century). The Tirumantiram is generally acknowledged to be a root text of the Tami Siddha tradition and it contains passages that elaborately discuss the theory and practices of yoga, presenting them as a means of attaining longevity and immortality. It also contains references to medical practices. Further, relevant ideas about rejuvenating, life-prolonging and immortalizing methods found in selected texts of the medico-alchemical stream of the tradition are discussed. The literature of the medical and alchemical lore of the Tamil Siddhas, roughly dated to the period between the 16th and 19th centuries, abounds in practical recipes for the drugs (kaṟpam) for prolonging life. Certain items credited with extraordinary powers connected with rejuvenation and immortalization, such as triple salt (muppu), mercurial jewel (racamaṇi), human urine, special varieties of medicinal plants, etc. are particularly referenced to in the paper. Finally, the concepts relating to “the art of non-dying” (cākākkalai) taught in the works of Vaḷḷalār, the poet-saint born in 19th century and closely linked with the Tamil Siddha tradition, are outlined in the article.